Plant growth-promoting actinobacterial inoculant assisted phytoremediation increases cadmium uptake in Sorghum bicolor under drought and heat stresses. (15th August 2022) - Silambarasan, Sivagnanam; Logeswari, Peter; Vangnai, Alisa S.; Kamaraj, Balu; Cornejo, Pablo
Abstract: In this study, two proficient Cadmium (Cd) resistant and plant growth-promoting actinobacterial strains were isolated from metal-polluted soils and identified as Streptomyces sp. strain RA04 and Nocardiopsis sp. strain RA07. Multiple abiotic stress tolerances were found in these two actinobacterial strains, including Cd stress (CdS), drought stress (DS) and high-temperature stress (HTS). Both actinobacterial strains exhibited multifarious plant growth-promoting (PGP) traits such as phosphate solubilization, and production of indole-3-acetic acid, siderophores and 1-aminocyclopropane-1-carboxylate deaminase under CdS, DS and HTS conditions. The inoculation of strains RA04 and RA07 significantly increased Sorghum bicolor growth and photosynthetic pigments under CdS, DS, HTS, CdS + DS and CdS + HTS conditions as compared to their respective uninoculated plants. The actinobacterial inoculants reduced malondialdehyde concentration and enhanced antioxidant enzymes in plants cultivated under various abiotic stress conditions, indicating that actinobacterial inoculants reduced oxidative damage. Furthermore, strains RA04 and RA07 enhanced the accumulation of Cd in plant tissues and the translocation of Cd from root to shoot under CdS, CdS + DS and CdS + HTS treatments as compared to their respective uninoculated plants. These findings suggest that RA04 and RA07 strains could be effective bio-inoculants to accelerate phytoremediation of Cd polluted soil even in DS and HTS conditions. Graphical abstract: Image 1 Highlights: Strains RA04 and RA07 are cadmium, drought and heat stress tolerant actinobacteria. It showed various plant growth-promoting traits even under abiotic stresses. It improved Sorghum bicolor growth under different abiotic stresses. It increased chlorophyll pigments and antioxidant enzymes in plants. It enhanced cadmium accumulation in S. bicolor under different abiotic stresses.